Numerical modeling of electric vehicles (BEVs) and fuel cell hybrid vehicles (FCHEVs) in ADVISOR: a brief literature review - Feroni, Wilson José; Feroni, Rita de Cassia; Romero, Oldrich Joel (Latin American Journal of Energy Research, 2025)
A literature review is presented on hydrogen fuel cell hybrid vehicles (FCHEVs) and battery electric vehicles (BEVs), based on numerical simulations carried out using the ADVISOR software. The investigation was conducted by selecting five articles, defined through bibliometric criteria following the Science Mapping methodology and the Web of Science and Scopus databases. The goal was to compare fuel consumption, performance, and greenhouse gas emissions of these two types of vehicles. ADVISOR, developed as a tool for simulating and analyzing the dynamic behavior of vehicles, makes it possible to evaluate different propulsion configurations, including electric vehicles, fuel cell hybrid vehicles, and models equipped with internal combustion engines (ICEVs). In this way, it serves as a comprehensive platform for comparative studies between electric and conventional mobility alternatives
Keywords: Advisor; hydrogen; numerical simulation; vehicles